Distilasi Uap untuk Meningkatkan Kualitas Minyak Kelapa Sawit (CPO) sebagai Upaya Menghasilkan Pembawa Sediaan Farmasi: Distilasi Uap untuk Meningkatkan Kualitas Minyak Kelapa Sawit (CPO) sebagai Upaya Menghasilkan Pembawa Sediaan Farmasi - Angelina Margaretha Ardiani; Isadiartuti, Dewi; Nuzul Wahyuning Diyah; Purnami, Nyilo (Universitas Airlangga, 2025)
Indonesia is the world's largest palm oil producer. In the pharmaceutical sector, palm oil has the potential to be used as an excipient in pharmaceutical dosage forms. Indonesian palm oil, which accounts for 58% of world production, has potential as a pharmaceutical excipient due to its fatty acid content and vitamin E, which have antibacterial and antioxidant activities. However, before being used as a carrier for pharmaceutical preparations, palm oil needs to meet SNI standards (specific gravity, water content, free fatty acids) and the Indonesian Pharmacopoeia (peroxide value, iodine value, refractive index). This study aims to purify CPO through two cycles of steam distillation and test the physicochemical parameters before and after the distillation process with One-Way ANOVA analysis at α = 0.05. Palm oil (CPO) was distilled at a temperature of 95 ± 0.5 °C for 4.5 hours. The palm oil that had been distilled twice was evaluated for oil quality. Research data shows that two-cycle distillation significantly reduces specific gravity, water content, free fatty acids, peroxide value, and iodine value. However, the resulting palm oil does not yet meet the requirements for pharmaceutical excipients. Steam distillation has been shown to improve CPO quality, but further processing, combined with other physical methods, is required to produce oil that meets pharmaceutical carrier standards. Keywords: Pharmaceutical Excipient, Palm Oil, Distillation, Crude Palm Oil (CPO), Free Fatty Acid